Preoperative predictive factors of cystobiliary fistulas in liver hydatid cysts: results of a monocentric study - Mohamed Salah Jarrar; Ines Karmani; Mehdi Chahed; Malek Barka; Mohamed Hedi Mraidha; Radhouane Toumi; Ameni Beizig; Khayri Dhouioui; Sabri Youssef (Future Science OA)
Introduction The evolution of hepatic hydatid cyst can be enameled with complications, mainly biliary fistula, which can be both symptomatic or occult. The aim of this study is to identify the predictive factors of occult cysto-biliary communication.Material and methods This is a retrospective study of patients operated-on for uncomplicated hepatic hydatid cyst in Farhat Hached Hospital of Sousse over a period of 10 years.Results Two hundred twenty patients were operated-on for uncomplicated hydatid cyst. In univariate analysis, alkaline-phosphatase, gamma-glutamyl-transferase, alanine-transferase elevated levels and multiple type were factors associated with occult fistula, but gamma-glutamyl-transferase level was the only predictor in multivariate analysis.Conclusion These predictive factors could contribute to determine preoperative probability of occult fistula, thus indicating additional intraoperative procedures to ensure its identification.